2022
DOI: 10.3390/biom12091304
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan as an Adjuvant to Enhance the Control Efficacy of Low-Dosage Pyraclostrobin against Powdery Mildew of Rosa roxburghii and Improve Its Photosynthesis, Yield, and Quality

Abstract: Powdery mildew is the most serious fungal disease of Rosa roxburghii in Guizhou Province, China. In this study, the control role of chitosan-assisted pyraclostrobin against powdery mildew of R. roxburghii and its influences on the resistance, photosynthesis, yield, quality and amino acids of R. roxburghii were evaluated. The results indicate that the foliar application of 30% pyraclostrobin suspension concentrate (SC) 100 mg L−1 + chitosan 500 mg L−1 displayed a superior control potential against powdery milde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…In our recent report, we found that 500 mg L −1 chitosan had a good control effect on R. roxburghii powdery mildew with an efficacy of 77.80% after 14 d of application [ 9 ]. Moreover, Zhang et al [ 34 ] found that 12.5~25.0 mg L −1 0.5% physcion AS had a significant inhibitory effect on R. roxburghii powdery mildew with the control efficacy of 77.01~82.26% after 14 d of application.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our recent report, we found that 500 mg L −1 chitosan had a good control effect on R. roxburghii powdery mildew with an efficacy of 77.80% after 14 d of application [ 9 ]. Moreover, Zhang et al [ 34 ] found that 12.5~25.0 mg L −1 0.5% physcion AS had a significant inhibitory effect on R. roxburghii powdery mildew with the control efficacy of 77.01~82.26% after 14 d of application.…”
Section: Methodsmentioning
confidence: 99%
“…The above-ground part of R. roxburghii plants was sprayed with 1.50 L of fungicide liquid or clear water on April 5 and 12 in 2022, respectively. The disease index and control efficacy of powdery mildew were respectively surveyed on, before, and after spraying according to Zhang et al [ 9 ]. The incidence levels were classified as: no incidence for 0 level, thin hyphae with 1~2 diseased lobules for 1 level, thick hyphae with 3~4 diseased lobules for 2 levels, dense hyphae with 5~6 diseased lobules for 3 levels, dense hyphae with exceeding 7 diseased lobules for 4 levels.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations